The discussion section of research articles in applied linguistics: Generic structure and stance features / Leila Dobakhti - Leila, Dobakhti (2011)
This thesis is a mixed-method genre-based study which analyzes the Discussion section of qualitative and quantitative research articles in the field of Applied Linguistics. It is particularly focused on examining the generic structures and stance features of these two sets of articles. The study consists of two main parts. In the first part, 15 qualitative and 15 quantitative RAs’ Discussion sections were analyzed employing Swales’ (1990, 2004) move structure model. In the second part of the study, Hyland’s (1999, 2005, 2008) taxonomy of stance features – hedges, boosters, attitude markers, and self mention – was used to investigate stance features. This part of the study was conducted in two sections. In the first part, using WordPilot 2002, these four stance features were investigated in two specialized sub-corpora of 100 qualitative and 100 quantitative research articles’ Discussion sections. The corpus analysis gave insightful information about the overall frequency as well as forms of stance features in the qualitative and quantitative sub-corpora. In the second part, in order to identify in which parts of the Discussion section each of these stance features were clustered in, these features were investigated in various moves of the Discussion sections of 10 qualitative and 10 quantitative research articles. Identifying the main moves in which each of these stance features occurred more frequently, helped to justify and account for the differences identified in the frequency of these features in 200 research articles. It also helped to identify the main function of these features based on the communicative purpose of the moves that the stance features appeared more frequently in. After the text analyses were completed, interviews were carried out with four specialist informants to supplement them. The aim of conducting these interviews was to obtain the insiders’ views on the conventions of the field and to verify the findings. Overall, the analysis revealed similarities as well as interesting differences between these two sets of articles in terms of generic structure and stance features. The differences and similarities can be attributed to the disciplinary conventions, different methodologies, and in the case of stance features to generic structure of these two sets of articles.